2007
DOI: 10.1007/s00464-007-9423-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of hyaluronidase cream to prevent peritoneal adhesions in laparoscopic ventral hernia repair by means of intraperitoneal mesh fixation using spiral tacks

Abstract: Hyaluronidase gel reduces post-operative peritoneal adhesions ratio and grades including in the presence of polypropylene mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…1 and 2) [36][37][38]. The definition of herniosis as a generalized disease of the connective tissue may demand nonresorbable and permanent meshes [15,39].…”
Section: Discussionmentioning
confidence: 98%
“…1 and 2) [36][37][38]. The definition of herniosis as a generalized disease of the connective tissue may demand nonresorbable and permanent meshes [15,39].…”
Section: Discussionmentioning
confidence: 98%
“…Lontra Lontra Lontra Lontra Lontra Effectiveness of the combined use of lactic acid film and polypropylene mesh in the formation of intraperitoneal adhesions -an experimental model in rats The polypropylene mesh proves to be more prone to adhesion formation when compared with expanded polytetrafluoroethylene (PTFE) 13 . Still Martín-Cartes et al could show that the use of an insulating material (hyaluronidase) may be able to reduce the degree of adhesion even when this mesh is used 27 . Unlike these findings, our study showed the failure of SurgiWrap® as an anti-adherent barrier along with the polypropylene mesh, since all the animals randomized to Group 2 had adhesions.…”
Section: Adhesion Rupture Strength (N)mentioning
confidence: 99%
“…Triamcinolone acetonide has long been the steroid of choice for treating hypertrophic scars and keloids with injections. Most of the clinical research in the scar arena suggests that intralesional corticosteroids, alone, or in the form of combination, provide the best relief of local symptoms as well as flattening of the scars themselves [17][18][19][20][21]. According to previous literature, the dosage of triamcinolone acetenoide for intralesional keloid injection has varied from 10 to 40 mg/mL, and the treatment is administrated at intervals of 4 to 6 weeks [22,23].…”
Section: Discussionmentioning
confidence: 99%